Serotonin A Chemical Messenger Between All Types of Living Cells - Fatima Shad, Kaneez (IntechOpen, 2017)
Serotonin - A Chemical Messenger Between All Types of Living Cells is a very interesting book on the most ancient neurotransmitter, hormone and trophic factor serotonin or 5-hydroxytryptamine (5-HT). This unique chemical is present in all living cells including plants and animals. This book will take us through a serene journey of the evolutionary history of serotonin and its role from man to mollusk. There are many interesting chapters incorporated in this book, including novel approaches for detecting minor metabolites of serotonin in human plasma, production and function of serotonin in cardiac cells, immuno-thrombotic effects of serotonin in platelets to the identification and localization of serotonin in the nervous system and gonad of bivalve mollusks.